Vestibular Manifestations In Retrocochlear Tumoral Pathology - Loreta Ungureanu; Luminita Radulescu; Sebastian Cozma; Costela Gegea; Dan Martu (Romanian Society of Oral Rehabilitation, 2012)
Introduction Retrocohlear tumoral pathology is dominated by the vestibular schwannoma (VS). The VS involve the vestibular division of the 8th cranial nerve and grows slowly leading to a gradual installation of the unilateral vestibular impairment allowing simultaneous achievement of central compensation process. Sometimes only a careful history will reveal a slow imbalance, a tendency to move towards to a certain lateral part. Remarkable progress has been made in the VS early diagnosis so that treatment can take place earlier with good results. Materials and methods A representative case is presented. Beside general, neurological and ENT examination, the diagnostic workup comprised of computerized dynamic posturography, videonystagmography, pure tone audiometry, auditory brainstem evoked response, MRI brainstem evaluation. Results In VS computerized dynamic posturography allows an overall of the vestibular function with polymorphic results. Bithermal caloric testing is, combined to auditory brainstem responses a good tool to diagnose and evaluate unilateral vestibular impairment in vestibular schwannoma. Discussion Detailed history, careful exploration of vestibular and cochlear function can lead to the conclusion of possible retrocochlear injury. For confirmation of its existence and its nature contrast-enhanced CT or MRI are necessary. Conclusion Any unilateral cochlear or vestibular symptoms (unilateral or asymmetric sensorineural hearing loss, unilateral tinnitus, unilateral vestibular impairment of any degree with central compensation or not) should raise suspicion of possible VS.